Atomic force microscopy and lamins: A review study towards future, combined investigations. Issue 1 (17th November 2016) - Pecorari, Ilaria; Puzzi, Luca; Sbaizero, Orfeo
Abstract: In the last decades, atomic force microscopy (AFM) underwent a rapid and stunning development, especially for studying mechanical properties of biological samples. The numerous discoveries relying to this approach, have increased the credit of AFM as a versatile tool, and potentially eligible as a diagnostic equipment. Meanwhile, it has become strikingly evident that lamins are involved on the onset and development of certain diseases, including cancer, Hutchinson‐Gilford progeria syndrome, cardiovascular pathologies, and muscular dystrophy. A new category of pathologies has been defined, the laminopathies, which are caused by mutations in the gene encoding for A‐type lamins. As the majority of medical issues, lamins, and all their related aspects can be considered as a quite complex problem. Indeed, there are many facets to explore, and this definitely requires a multidisciplinary approach. One of the most intriguing aspects concerning lamins is their remarkable contribute to cells mechanics. Over the years, this has led to the speculation of the so‐called "structural hypothesis", which attempts to elucidate the etiology and some features of the laminopathies. Among the various techniques tried to figure out the role of lamins in the cells mechanics, the AFM has been already successfully applied, proving its versatility. Therefore, the present work aims both to highlight the qualities of AFM and to review the most relevant knowledge about lamins, in order to promote the study of the latter, taking advantage from the former. Microsc. Res. Tech. 80:97–108, 2017 . © 2016 Wiley Periodicals, Inc.